Manipulation for synchronization of flowering of parental lines of sunflower (Helianthus annuus) hybrid - Chakrabarty, S K; Vari, A K; Sharma, S P (The Indian Journal of Agricultural Sciences, 2005)
Experiments were conducted to study synchronization of flowering in parental lines of sunflower (Helianthus annuus hybrid ’KBSH 1 ’ having a gap of 7-11 days in flowering under different agro-climatic conditions. Seed treatment with simple hydration to the female parent and with GA3 (50 ppm) to the male parent for 18 hours before sowing and spraying urea (1%) thrice on alternate days at the button formationw stage to the male parent resulted in a good degree of synchrony in flowering between the parental lines. The optimum sowing time suggested is first fortnight of January under northern India conditions.